PENGARUH INFRA RED DENGAN MASSAGE FISIOTERAPI TERHADAP TINGKAT STRES MAHASISWA YANG SEDANG MENGERJAKAN TUGAS AKHIR - Zuyina Lukluk Aningsih (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
The Effect of Infra-Red with Physiotherapy Massage on the Stress Level of Students Who Are Working on Final ProjectsBackground: Students who are working on final assignments often experience stress because they feel tired, anxious, are not enthusiastic about doing their final assignments, so they sometimes choose to forget about them, avoid their supervisors, complain about social media about the difficulties they are facing and ultimately cause delays in the study period. Objective: This study aims to determine the effect of infrared massage with physiotherapy on stress levels in students who are working on their final project. Methods: This study used a pre-experimental design. Data collection tools using interviews and questionnaires. Data analysis techniques used univariate and bivariate analysis (Wilcoxon test). Results: The results of the study concluded that infrared luminous massage with physiotherapy can reduce the stress level of students who are working on their final project. Conclusion: Infra red luminous massage with physiotherapy can reduce the stress level of students who are working on final assignments.